Squamous cell carcinoma of the lower lip: Excision and reconstruction with nasolabial flap - Emiliano José Canton; Marcelo Lima Pupo Nogueira; Rafael Resende Pereira; Denilson Marcos Cúrcio (Revista Brasileira de Cirurgia Plástica)
Introduction: Squamous cell carcinoma is the most common malignant tumor of the lips and mainly affects the lower lip. Adequate treatment of this neoplasm must be early and radical, as metastases can occur. Considering that the lips are extremely important in the dynamics and motricity of the face, lip reconstruction after major resections in this region is a challenge for the surgeon in the search for good aesthetic and functional results. This study seeks to present an already established and reliable technique for reconstructing the lower lip after tumor resection, the Karapandizic flap. Method: In this case review, 4 patients with lower lips reconstructed using the Karapandzic technique in 2013-2022 are retrospectively evaluated. Results: The most frequently observed complications were hypertrophic scar, lip vermilion suture dehiscence, and microstomia (reduction of oral opening). The cleft lip (microstomia) reduction was partially corrected through dental orthoses, with no need for commissuroplasty in any of the cases. Another contribution of this work is the use of preoperative color echoDoppler, which allows flap planning by checking the viability of the vascular pedicle and the actual positioning of this pedicle, reducing the chances of inadvertent injury to the vessels during surgery. Conclusion: Even though microstomy is a limitation of this flap, we conclude that this technique meets the need for lower lip reconstruction in large resections, as it can provide satisfactory results in oncological, functional, and aesthetic terms.